2007
DOI: 10.1160/th06-08-0470
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction induced in endothelial cells by growth factor receptors involved in angiogenesis

Abstract: SummaryNew vessel formation during development and in the adult is triggered by concerted signals of largely endothelial-specific receptors for ligands of the VEGF, angiopoietin and ephrin families. The signals and genes induced by these receptors operate in the context of additional signals transduced by non-endothelial specific growth factor receptors, inflammatory cytokine receptors as well as adhesion molecules. We summarize here available data on characteristic signaling of the VEGF receptor-2 and the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 111 publications
0
38
0
Order By: Relevance
“…Tumor angiogenesis principally relies on vascular endothelial growth factor (VEGF)-driven angiogenic responses, which lead to a dysfunctional vasculature [[70]]. Moreover, the invasion of endothelial cells (ECs) occurs after the release of matrix metalloproteinase 2 and 9 (MMP2/9), which destroy and degrade the basal membrane and extracellular matrix, finally resulting in the migration of ECs and the formation of neovessels [[71]].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor angiogenesis principally relies on vascular endothelial growth factor (VEGF)-driven angiogenic responses, which lead to a dysfunctional vasculature [[70]]. Moreover, the invasion of endothelial cells (ECs) occurs after the release of matrix metalloproteinase 2 and 9 (MMP2/9), which destroy and degrade the basal membrane and extracellular matrix, finally resulting in the migration of ECs and the formation of neovessels [[71]].…”
Section: Introductionmentioning
confidence: 99%
“…Tip cells migrate out of the vessel wall followed by proliferating stalk cells eventually forming a new capillary [3]. VEGF-A/VEGFR2 signaling has been shown to strongly activate the PKC/MAPK and Ca ++ /NFAT pathways via PLC-gamma as well as the PI3K/AKT pathway to induce migration, proliferation and survival [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…PLC-Îł in turn leads to calcium release and activation of protein kinase C (PKC) pathways. These pathways induce the transcription factors NFAT and EGR-1, respectively, to trigger the angiogenic response (Hofer and Schweighofer, 2007; Machtcheriakova et al, 1999; Mechtcheriakova et al, 2001). PLC-Îł/PKC also activate protein kinase D (PKD) phosphorylation of histone deacetylase 7 (HDAC7) resulting in endothelial cell proliferation and migration (Wang et al, 2008).…”
Section: Signaling In Vasculogenesismentioning
confidence: 99%
“…However, other studies suggested a mitogenic role for TGFβ on endothelial cells (Iruela-Arispe and Sage, 1993; RayChaudhury and D’Amore, 1991; Sutton et al, 1991). These differences in TGFβ action could be due to differences in dose since low doses of TGFβ upregulate angiogenic factors, whereas high doses appear to inhibit endothelial cell growth (Hofer and Schweighofer, 2007). Contradictory results were also observed in vivo with studies showing both pro-angiogenic and anti-angiogenic roles for TGFβ (Li et al, 2001; Roberts et al, 1986).…”
Section: Signaling In Vasculogenesismentioning
confidence: 99%